Experience with Emergency Ultrasound Training by Canadian Emergency Medicine Residents - Kim, Daniel J. (Department of Emergency Medicine, University of California, Irvine, 2014)
Introduction: Starting in 2008, emergency ultrasound (EUS) was introduced as a core competency to the Royal College of Physicians and Surgeons of Canada (Royal College) emergency medicine (EM) training standards. The Royal College accredits postgraduate EM specialty training in Canada through 5-year residency programs. The objective of this study is to describe both the current experience with and the perceptions of EUS by Canadian Royal College EM senior residents. Methods: This was a web-based survey conducted from January to March 2011 of all 39 Canadian Royal College postgraduate fifth-year (PGY-5) EM residents. Main outcome measures were characteristics of EUS training and perceptions of EUS. Results: Survey response rate was 95% (37/39). EUS was part of the formal residency curriculum for 86% of respondents (32/37). Residents most commonly received training in focused assessment with sonography for trauma, intrauterine pregnancy, abdominal aortic aneurysm, cardiac, and procedural guidance. Although the most commonly provided instructional material (86% [32/37]) was an ultrasound course, 73% (27/37) of residents used educational resources outside of residency training to supplement their ultrasound knowledge. Most residents (95% [35/37]) made clinical decisions and patient dispositions based on their EUS interpretation without a consultative study by radiology. Residents had very favorable perceptions and opinions of EUS. Conclusion: EUS training in Royal College EM programs was prevalent and perceived favorably by residents, but there was heterogeneity in resident training and practice of EUS. This suggests variability in both the level and quality of EUS training in Canadian Royal College EM residency programs. [West J Emerg Med. 2014;15(3):306–311.]